2010
DOI: 10.1007/s11910-010-0166-7
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Pituitary Tumors and Headache

Abstract: Pituitary tumors may give rise to headache via numerous mechanisms. The traditional explanation for headache is dural stretch and cavernous sinus invasion, although this is not borne out by clinical studies. Certain functional pituitary tumors are associated with headache, notably growth hormone and prolactin-secreting tumors. The observation that somatostatin analogues can have a dramatic analgesic effect in acromegaly suggests that biochemical properties of the tumor may be important. The genetic predisposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 47 publications
0
39
1
Order By: Relevance
“…29 It is also known that dopamine agonist therapy may improve migraine as well as markedly exacerbate headache in treatment of prolactinomas. 24 We found no hormone related variables that were associated with headache either before the diagnosis or at follow-up. However, hormone deficiencies were classified based on the interpretation of laboratory tests stated in the medical records and not assessed systematically or prospectively.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…29 It is also known that dopamine agonist therapy may improve migraine as well as markedly exacerbate headache in treatment of prolactinomas. 24 We found no hormone related variables that were associated with headache either before the diagnosis or at follow-up. However, hormone deficiencies were classified based on the interpretation of laboratory tests stated in the medical records and not assessed systematically or prospectively.…”
contrasting
confidence: 56%
“…3 Headache is a common cause for undergoing diagnostic cerebral MRIs that may lead to the incidental discovery of pituitary adenomas. 24 A recent retrospective study found that 24% of patients with pituitary tumours had headache as their chief complaint before surgery. 25 In the present study 12% of our patients had headache as the main symptom leading to the diagnostic MRI, presumably contributing to the higher prevalence of headache than in the general population at diagnose.…”
mentioning
confidence: 99%
“…Mechanical, biochemical, vascular and biopsychosocial aspects, and also a genetic predisposition for primary headache might be involved in the pathogenesis of headache in pituitary disease (1). Among functional pituitary tumours, growth hormone (GH)-secreting adenomas and prolactinomas have been specifically associated with headache, possibly mediated by the change in endocrine status rather than the pituitary mass per se (2). Transsphenoidal surgery may lead to significant improvement in headache in patients with non-secreting and hypersecretory pituitary microadenomas (3).…”
Section: Introductionmentioning
confidence: 99%
“…Dislalia was found in 1 patient, right palpebral ptosis in 1 patient, and headache in 41 patients (26.28%); the relationship between headache and IV-E stage of H-V classification was significant (p < 0.017). This relationship disappeared within 6 months in 30 of the patients after neurosurgery [16]. A tumor extension to the III ventricle was observed in 16 cases (10.26%), diabetes insipidus in 4 patients (2.56%), and pituitary apoplexy in 11 cases (7.05%).…”
Section: Resultsmentioning
confidence: 94%